Mean recurrence interval as a criterion for the determination of design wind load on structures in the Metro Manila area - Villasenor, Vinci Nicholas R.
The thesis presents some probabilistic methods of determining the basic design wind load as an alternative to the current deterministic wind speed of 175 kph for the Metro_manila area as specified by the National Structural Code for Buildings (NSCB). Other engineering codes have recognized the need to specify wind loading based on the probabilistic concepts consisted with the code's objective of providing consistent and adequate levels of safety. The mean recurrence interval as the design criterion for the determination of wind loading is proposed in keeping with the continuously improving standards of other engineering codes.
The basic design wind speed specification of the NSCB is discussed. Model parameters of the Gumbel and Frechet distributions (Type I and Type II distributions of the largest values respectively) are estimated using annual maximum wind speed data obtained from the three weather stations of the Philippines Atmospheric Geophysical, and Astronomical Services Administration (PAGASA) in Metro-Manila. Two sets of parameter values are determined for the Gumbel distribution; the parameters derived by the Lieblein fitting technique and the parameters derived by the method of moments. The Kolmogrov-Smirnov goodness-of-fit test is used to determined the acceptability of the probabilistic models and the Gumbel distribution (Type II distribution of the largest values) is found to best model annual maximum winds in Metro-Manila. The basic design wind speeds corresponding to suggested values of mean recurrence intervals are computed based on the probabilistic model chosen.
Thesis (M.S. )--University of the Philippines, Diliman.
Typescript.
Keywords: Wind-pressure.; Winds -- speed -- Philippines -- Manila Metropolitan Area